2007
DOI: 10.1021/jf070257h
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids and Biflavonoids in Tuscan Berries of Juniperus communis L.:  Detection and Quantitation by HPLC/DAD/ESI/MS

Abstract: The aim of the present work was to develop a quali-quantitative investigation, using HPLC/DAD and HPLC/ESI/MS techniques, of the phenolic composition of berries collected from wild Tuscan plants of Juniperus communis L. and grown in three different geographical zones. The applied chromatographic elution method made it possible to well separate up to 16 different compounds belonging to flavonoids, such as isoscutellarein and 8-hydroxyluteolin or hypolaetin glycosides, and six biflavonoids, among them amentoflav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 19 publications
2
26
1
2
Order By: Relevance
“…2). These compounds, eluted in fractions 4, 5, 7, 9, 10 and 11, showed characteristic UV spectra with maxima at 278, 302 and 333 nm, which is in agreement with that described for isoscutellarein glucosides (Innocenti et al, 2007;Sahin, Ezer, & Calis, 2006;Saracoglu, Harput, & Ogihara, 2004). Notably, this is the first study reporting this flavonoid aglycone class in the Lamium genus, refuting previous chemotaxonomic studies of the plant (Tomás-Barberán, Grayer-Barkmeijer, Gil, & Harborne, 1988).…”
Section: Isoscutellarein Derivativessupporting
confidence: 84%
“…2). These compounds, eluted in fractions 4, 5, 7, 9, 10 and 11, showed characteristic UV spectra with maxima at 278, 302 and 333 nm, which is in agreement with that described for isoscutellarein glucosides (Innocenti et al, 2007;Sahin, Ezer, & Calis, 2006;Saracoglu, Harput, & Ogihara, 2004). Notably, this is the first study reporting this flavonoid aglycone class in the Lamium genus, refuting previous chemotaxonomic studies of the plant (Tomás-Barberán, Grayer-Barkmeijer, Gil, & Harborne, 1988).…”
Section: Isoscutellarein Derivativessupporting
confidence: 84%
“…Regarding the TFC, the juniper (2.25 ± 0.01 mg QE/g dw) contains more flavonoids as compared to hops (1.37 ± 0.01 mg QE/g dw). Previously, only a few flavonoids were detected in hops [7] while flavonoids were considered as the major polyphenol classes in juniper berries [9]. Nasri et al [19] also reported a higher concentration of total flavonoids (8.90 ± 0.48 mg/g dw) from juniper berries (Juniperus phoenicea), it was found that different juniper varieties have different flavonoids content.…”
Section: Polyphenol Estimation (Tpc Tfc and Ttc)mentioning
confidence: 97%
“…has attracted significant interest (Angioni et al, 2003;Cavaleiro et al, 2001Cavaleiro et al, , 2002Cavaleiro et al, , 2003Rezzi et al, 2001;Salido et al, 2002;Tunalier, Kirimer, & Baser, 2003) much less attention has been paid to other components and there is paucity of detail on the phenolic characterization of Juniperus sp. Previous reports have highlighted the presence of phenolic compounds including flavonoids, neolignans and phenylpropanoids (Iida et al, 2007;Innocenti et al, 2007;Lamerzarawska, 1975;Nakanishi et al, 2004;Sakar & Friedrich, 1984), but also terpenoids (Nunez, Salabarria, Collado, & Hernandez-Galan, 2007;Okasaka et al, 2006;Seca, Silva, Bazzocchi, & Jimenez, 2008). Studies on Juniperus species occurring in Portugal have been even more limited and the focus again was on essential oils (Cavaleiro et al, , 2002(Cavaleiro et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%